2015
DOI: 10.5194/acp-15-5007-2015
|View full text |Cite
|
Sign up to set email alerts
|

Lidar profiling of aerosol optical properties from Paris to Lake Baikal (Siberia)

Abstract: Abstract. In June 2013, a ground-based mobile lidar performed the ∼ 10 000 km ride from Paris to Ulan-Ude, near Lake Baikal, profiling for the first time aerosol optical properties all the way from western Europe to central Siberia. The instrument was equipped with N 2 -Raman and depolarization channels that enabled an optical speciation of aerosols in the low and middle troposphere. The extinction-to-backscatter ratio (also called lidar ratio or LR) and particle depolarization ratio (PDR) at 355 nm have been … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 54 publications
2
47
0
Order By: Relevance
“…Three aerosol types are considered: (i) dust-like aerosols with values of BER and PDR centred on 0.022 sr −1 and 20 %, respectively, (ii) pollution aerosols with BER and PDR centred on 0.015 sr −1 and 2 %, respectively, and (iii) marine aerosols with mean values of BER and PDR centred on 0.04 sr −1 and 0 %, respectively. For each aerosol type, literature sometimes reports a large range of values, as shown in Tables 1 and 3 of Dieudonné et al (2015) for dust and pollution aerosols, respectively. These authors report at the same wavelength BER from 0.013 to 0.026 sr −1 and PDR from 13 to 25 % for pure dust or dusty mix (0.011-0.017 sr −1 and 3-5 %, respectively, for pollution) aerosols.…”
Section: Evidence Of Contributions By Aerosol Type As Discriminated Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Three aerosol types are considered: (i) dust-like aerosols with values of BER and PDR centred on 0.022 sr −1 and 20 %, respectively, (ii) pollution aerosols with BER and PDR centred on 0.015 sr −1 and 2 %, respectively, and (iii) marine aerosols with mean values of BER and PDR centred on 0.04 sr −1 and 0 %, respectively. For each aerosol type, literature sometimes reports a large range of values, as shown in Tables 1 and 3 of Dieudonné et al (2015) for dust and pollution aerosols, respectively. These authors report at the same wavelength BER from 0.013 to 0.026 sr −1 and PDR from 13 to 25 % for pure dust or dusty mix (0.011-0.017 sr −1 and 3-5 %, respectively, for pollution) aerosols.…”
Section: Evidence Of Contributions By Aerosol Type As Discriminated Bmentioning
confidence: 99%
“…Two validated (e.g. Dieudonné et al, 2015) measurement synergy types have been used to retrieve the aerosol optical properties from the lidar. During daytime the sun-photometer AOT 355 is considered as a constraint for the lidar inversion as in Chazette (2003).…”
Section: Raman Lidarmentioning
confidence: 99%
“…Lidar measurements along the Caspian and Aral Sea region and Lake Balkhash in Kazakhstan were performed by Dieudonné et al (2015). Dieudonné et al (2015) showed that dust layers originating in the Caspian and Aral Sea region can regularly spread over wide areas of Russia and last for several days.…”
Section: Introductionmentioning
confidence: 99%
“…A lidar is operated in Aksu (northwestern Taklamakan; Kai et al, 2008), where local dust was measured from ground to a height of 6 km during strong dust outbreaks as well as lofted long-range transported dust layers at heights of 11 km (Mikami et al, 2006). Lidar measurements along the Caspian and Aral Sea region and Lake Balkhash in Kazakhstan were performed by Dieudonné et al (2015). Dieudonné et al (2015) showed that dust layers originating in the Caspian and Aral Sea region can regularly spread over wide areas of Russia and last for several days.…”
Section: Introductionmentioning
confidence: 99%
“…We have noted the dispersion in the PBL of dust-like aerosols is efficient during the afternoons with mean vertical speed velocity larger than 1 ms -1 . This study has to be continued and the aerosol optical properties retrieved by the lidar measurements in terms of PDR and BER should be compared to those we met within London [6] and during the experiment conducted from Paris (France) to the lake Baikal (Russia) in 2013 [7].…”
Section: Conclusive Discussionmentioning
confidence: 99%